2017
DOI: 10.18632/oncotarget.20216
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of millet bran derived-bound polyphenols in LPS-induced HT-29 cell via ROS/miR-149/Akt/NF-κB signaling pathway

Abstract: The pro-inflammatory and anti-inflammatory maladjustment has been acknowledged as one of the chief causations of inflammatory diseases and even cancers. Previous studies showed that plant-derived polyphenolic compounds were the most potent anti-oxidant and anti-inflammatory agents among all natural compounds. The present study indicates that bound polyphenols of inner shell (BPIS) from foxtail millet bran can display anti-inflammatory effects in LPS-induced HT-29 cells and in nude mice. Mechanistically, BPIS r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 47 publications
3
31
0
Order By: Relevance
“…MicroRNA-21a, miR-146b, and miR-149 were highlighted as those miRNAs with the most prominent increase upon 3R4F CS versus sham in lung compared with the other tissues. For all 3 miRNAs, an association with immune-responses have been reported: miR-21a is a negative immune regulator in mouse liver regeneration (via nuclear factor kappa B [NF-κB] inhibition) ( Marquez et al 2010 ) and of the macrophage response in peritonitis ( Barnett et al 2016 ), miR-146b is an innate immune cell-associated miRNA ( Hou et al 2009 ), and miR-149 has been implicated in immune-regulatory feedback loops ( Shi et al 2017 ; Xu et al 2014 ). Overall, this is consistent with the prominent immune response observed in the lung upon 3R4F CS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-21a, miR-146b, and miR-149 were highlighted as those miRNAs with the most prominent increase upon 3R4F CS versus sham in lung compared with the other tissues. For all 3 miRNAs, an association with immune-responses have been reported: miR-21a is a negative immune regulator in mouse liver regeneration (via nuclear factor kappa B [NF-κB] inhibition) ( Marquez et al 2010 ) and of the macrophage response in peritonitis ( Barnett et al 2016 ), miR-146b is an innate immune cell-associated miRNA ( Hou et al 2009 ), and miR-149 has been implicated in immune-regulatory feedback loops ( Shi et al 2017 ; Xu et al 2014 ). Overall, this is consistent with the prominent immune response observed in the lung upon 3R4F CS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…TNF- α , IL-6, IL-1 β , and PGE2 expression in the cultured cell supernatants was quantified using an enzyme-linked immunosorbent assay (ELISA) kit (Quantikine® ELISA, R&D Systems, MN, USA) [ 18 ] according to the manufacturer's instructions. Absorbance was measured at 450 nm using a FlexStation 3 microplate reader (Molecular Devices, USA).…”
Section: Methodsmentioning
confidence: 99%
“… 9 An animal experiment showed that foxtail millet feeding improved insulin sensitivity and cholesterol metabolism in genetically type 2 diabetic mice. 10 A recent study indicated that bound polyphenols of inner shell from foxtail millet bran can display anti-inflammatory effects in LPS-induced HT-29 cells and in nude mice, 11 another clinical trial have shown the blood glucose lowering of foxtail millet. 12 …”
Section: Introductionmentioning
confidence: 99%